Dr. Edwin Wright Letters: Allan Bowe - (Author); (Interviewer); (Publisher) (1961)
Letter - Mr. Bowe writes of life in Athabasca Landing from 1910 on-wards. He discusses the local businesses, land transactions, and what life and work was like at that time (2 pages)